2015
DOI: 10.1093/annonc/mdv191
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in initiating and conducting personalized cancer therapy trials: perspectives from WINTHER, a Worldwide Innovative Network (WIN) Consortium trial

Abstract: Advances in 'omics' technology and targeted therapeutic molecules are together driving the incorporation of molecular-based diagnostics into the care of patients with cancer. There is an urgent need to assess the efficacy of therapy determined by molecular matching of patients with particular targeted therapies. WINTHER is a clinical trial that uses cutting edge genomic and transcriptomic assays to guide treatment decisions. Through the lens of this ambitious multinational trial (five countries, six sites) coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 40 publications
1
62
0
1
Order By: Relevance
“…24,25), aimed at selecting optimal innovative drug treatment strategies for patients with advanced metastatic tumors, has highlighted the utility of sampling matched normal and tumor biopsies from the same patient to identify novel therapeutic strategies based on differential gene expression in the neoplastic tissue compared with the normal sample. There are a number of clear similarities between the WINTHER study approach and the findings presented here, where the nontumor component can inform prognosis, but although there seems to be clear rationale for this approach aimed at personalized drug selection, there may be only limited benefit derived by subtracting the results of adjacent normal or stromal tissue to correctly classify the overall tumor molecular subtype.…”
Section: Implications Of Transcriptomic Heterogeneity Within Colorectmentioning
confidence: 99%
“…24,25), aimed at selecting optimal innovative drug treatment strategies for patients with advanced metastatic tumors, has highlighted the utility of sampling matched normal and tumor biopsies from the same patient to identify novel therapeutic strategies based on differential gene expression in the neoplastic tissue compared with the normal sample. There are a number of clear similarities between the WINTHER study approach and the findings presented here, where the nontumor component can inform prognosis, but although there seems to be clear rationale for this approach aimed at personalized drug selection, there may be only limited benefit derived by subtracting the results of adjacent normal or stromal tissue to correctly classify the overall tumor molecular subtype.…”
Section: Implications Of Transcriptomic Heterogeneity Within Colorectmentioning
confidence: 99%
“…29 Preliminary reports from such studies highlight difficulties in providing appropriate treatment to match disease complexity and probability of response, choosing the right patients, defining relevant outcomes, overcoming regulatory and logistic hurdles, and aggregating results to generate and share new knowledge about actionable mutations and biomarkers of disease resistance and evolution. [7][8][9][10][11] In fact, an interim analysis of the National Cancer Institute-Molecular Analysis for Therapy Choice (NCI-MATCH) trial demonstrated that after screening nearly 800 patients, only 9% were found to harbor a study-targeted actionable mutation. 8 Other studies reported higher, but still limited, match rates.…”
Section: Basket Clinical Trial Designsmentioning
confidence: 99%
“…1.3 has been considered clinically meaningful. 7,58,59 In one such basket trial, Von Hoff et al 58 reported that 27% of patients achieved this end point with a median PFS targeted :PFS prior line ratio of 2.9. Of note, the overall response rate was only 10%.…”
Section: Definition Of Appropriate Outcomesmentioning
confidence: 99%
See 2 more Smart Citations